OP10 Assessing models of ACP in primary care, the meta-LARC trial: part 4 cross us-canada ethics challenges and experience. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Totten, A; Michaels, L; Caron, D; Guay-Belanger, S; Grant, K; Greiver, M
Abstract : Background: We designed a collaborative, US-Canadian study to increase generalizability and explicitly consider potential for spread across different systems. Addressing ethical requirements for multiple Institutional Review Boards (IRBs) and Research Ethics Boards (REBs) presents challenges when conducting one trial in two countries. Methods: Our trial includes 42 primary care practices from practice-based research networks (PBRNs) in 5 US states and 2 Canadian provinces. A centralized, single IRB process was used in the US with Clinical and Translational Science Award authorization to the PI for the 5 IRBs to rely on one unassociated IRB. In Canada ethics oversight required different approaches in each province. Ontario used a partially centralized and an institutional REB while Quebec used a fully centralized REB. Similar study protocols were submitted to all IRBs/REBs. The joint coordinating center harmonized research workflows and procedures to respond to a variety of concerns and requests. Results: The number and nature of concerns requiring clarifications and modifications varied across the IRBs and REBs. The IRBs/REBs considered the trial to present different levels of risk and viewed the training, implementation and evaluation of ACP differently. There were differences regarding informed consent, survey language and data sharing. While the process and approvals took longer than expected and posed issues for consistency, addressing them facilitated development of a robust intervention and protocol. Conclusion: Differences in research ethics perspectives and procedures could be significant barriers to US-Canada research. We demonstrated that variation could be addressed, knowledge-sharing strengthened the project protocol, and future collaborations are possible.